Identification of pharmaceuticals in landfill leachates – screening test - Nowak, Rafał; Włodarczyk-Makuła, Maria (Instal, 2025)
Currently, a number of researchers are involved in identifying sources of pharmaceutical contamination in the aquatic environment and assessing the level of contamination of water bodies. The update of the Wastewater Directive on wastewater treatment includes, among other things, the monitoring of concentrations of selected pharmaceuticals. However, the scope of analysis is limited to the determination of 12 compounds, but other active compounds from this group of micropollutants are also identified in wastewater. The aim of this study was to identify pharmaceuticals in landfill leachate collected from an example landfill site. Qualitative-quantitative determination was carried out using liquid chromatography with an MS/MS detector. The qualitative analysis identified the presence of 88 compounds belonging to different groups of active compounds: non-steroidal anti-inflammatory drugs, anticonvulsants, benzodiazepine derivatives, antibiotics, opioid analgesics, antiparasitics, cytostatics, β-blockers, androgenic hormones, iodine contrast agents and others. Quantitative analysis of individual compounds showed varying concentrations: from less than the limit of quantification to 25 μg/dm3.
Keywords: micropollutants; pharmaceutics; personal care products; landfill leachate; municipal solid waste landfills; LC-MS/MS